2022
DOI: 10.1038/s41556-022-00925-9
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic enzyme hexokinase 2 localizes to the nucleus in AML and normal haematopoietic stem and progenitor cells to maintain stemness

Abstract: Mitochondrial metabolites regulate leukaemic and normal stem cells by affecting epigenetic marks. How mitochondrial enzymes localize to the nucleus to control stem cell function is less understood. We discovered that the mitochondrial metabolic enzyme hexokinase 2 (HK2) localizes to the nucleus in leukaemic and normal haematopoietic stem cells. Overexpression of nuclear HK2 increases leukaemic stem cell properties and decreases differentiation, whereas selective nuclear HK2 knockdown promotes differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 72 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…Overexpressed HK2 has been found to promote, upon its nuclear localization, a stem cell phenotype in both acute myeloid leukemia (AML) and normal hematopoietic cells [ 113 ]. This was the consequence of HK2 becoming phosphorylated and having interacted with nuclear proteins known to regulate chromatin accessibility, leading to increased chromatin accessibility at DNA domains promoting stemness and DNA repair.…”
Section: Can Upregulated Glycolysis Play a Causative Role In Oncogene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpressed HK2 has been found to promote, upon its nuclear localization, a stem cell phenotype in both acute myeloid leukemia (AML) and normal hematopoietic cells [ 113 ]. This was the consequence of HK2 becoming phosphorylated and having interacted with nuclear proteins known to regulate chromatin accessibility, leading to increased chromatin accessibility at DNA domains promoting stemness and DNA repair.…”
Section: Can Upregulated Glycolysis Play a Causative Role In Oncogene...mentioning
confidence: 99%
“…Histone O -GlcNacylation has also been shown to influence the chromatin structure and regulate gene expression [ 119 ]. Eventually, the effect of nuclear HK2 leading to an increase in open chromatin conformation has been discussed before [ 113 ].…”
Section: Mechanistic Aspects Of the Involvement Of Glycolysis In Earl...mentioning
confidence: 99%
“…[SPIN1]), transcriptional regulators (e.g., interacts with Spt6 [IWS1]), and DNA damage responders (e.g., Sirtuin-1 [SIRT1]). The overall effect is to enhance chromatin accessibility to an array of HR-mediated repair proteins (Thomas et al, 2022). The next glycolytic enzyme with prominent influences on DSB repair is PFKFB3.…”
Section: Glycolysis Is the Metabolic Coordinator That Favors Homologo...mentioning
confidence: 99%
“…Beginning with hexokinase‐2 (HK2), this first enzyme of the glycolysis can be phosphorylated and subsequently translocated into the nucleus to regulate chromatin openness via interacting with other nuclear proteins, including chromatin organizers (e.g., Myc‐associated factor X [MAX] and spindling‐1 [SPIN1]), transcriptional regulators (e.g., interacts with Spt6 [IWS1]), and DNA damage responders (e.g., Sirtuin‐1 [SIRT1]). The overall effect is to enhance chromatin accessibility to an array of HR‐mediated repair proteins (Thomas et al, 2022). The next glycolytic enzyme with prominent influences on DSB repair is PFKFB3.…”
Section: The Central Carbon Metabolism Supports Ddr In Multiple Aspectsmentioning
confidence: 99%
“…Accumulated evidence has indicated that glucose metabolism and the expression of HK2 may promote tumor chemoresistance. 12,13 By increasing the ubiquitination of pleckstrin homeodomain leucine-rich repeat protein phosphatase 2 and upregulating the expression of p-AKT, overexpression of wild-type tripartite motif 46 can promote the proliferation and glycolysis of lung adenocarcinoma (LUAD) cells and enhance their resistance to cisplatin. 14 Knockdown of HK2 expression can enhance the sensitivity of ovarian cancer to cisplatin.…”
Section: Introductionmentioning
confidence: 99%